Promoter polymorphism in the serotonin transporter (5-HTT) gene is significantly associated with leukocyte telomere length in Han Chinese. - Ping Li; Tiantian Liu; Jiajia Liu; Qing Zhang; Fenglan Lou; Feng Kong; Guanghui Cheng; Magnus Björkholm; Chengyun Zheng; Dawei Xu (PLoS ONE, 2014)
The serotonin transporter gene (5-HTT)-linked polymorphic region (5-HTTLPR) plays an important role in modulating mood and behavior by regulating 5-HTT expression and thereby controlling the concentration of serotonin (5-HT) in brain synapses: The homozygous shorter allele (S/S) in 5-HTTLPR results in lower 5-HTT expression coupled with stronger psycho-pathological reactions to stressful experiences compared to the homozygous long (L/L) and heterozygous (S/L) alleles. Psychological insults and mood disorders have been shown to cause accelerated telomere shortening, a marker of biological aging, however, it is currently unclear whether the allelic variants of 5-HTTLPR affect telomere length (TL) in the healthy population without mood disorders. In the present study, we determined the relationship between TL and the 5-HTTLPR variants in healthy Han Chinese. The 5-HTTLPR genotyping and leukocyte TL analysis of 280 young female Han Chinese freshmen showed a significantly shorter TL in 149 of them carrying the 5-HTTLPR S/S version compared to those (131) with the L/S or L/S plus L/L genotypes (mean ± SD, 0.533±0.241 for S/S vs 0.607±0.312 for L/S, P  =  0.034; or vs 0.604±0.313 for L/S plus L/L, P  =  0.038). Similar results were achieved in the other cohort including 220 adult healthy individuals of different age, gender and profession (0.691±0.168 for S/S vs 0.729±0.211 for L/S, P  =  0.046, or vs 0.725±0.213 for L/S plus L/L, P  =  0.039). Taken together, shorter leukocyte TL is significantly associated with the 5-HTTLPR S/S allelic variant, which may be implicated in psychological stress-related health problems.